Madoxychara gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), a new genus of the tribe Phantiini Melichar from Madagascar - Stroiński, Adam; Świerczewski, Dariusz (Zootaxa, 2013)
Madoxychara unicornis gen. et sp. nov. (Hemiptera: Fulgoromorpha: Flatidae) is described and illustrated from Madagascar.